Use of Cognitive Simulation During Anesthesiology Resident Applicant Interviews to Assess Higher-Order Thinking - Kulig, Alan W. (J Grad Med Educ, 2016)
BACKGROUND: It is difficult to assess applicants' higher-order cognitive thinking skills during conventional resident interviews. Application metrics currently employed are useful indicators of academic and personal success in targeted areas, yet value of this information in predicting future clinical performance is limited. OBJECTIVE: We developed an assessment tool to evaluate higher-order cognitive function in real time during anesthesiology resident applicant interviews. METHODS: During the 2014–2015 residency interview season, we integrated simulation training into applicant interviews to evaluate higher-order cognitive skills. Our 5-minute simulation emphasized the Team STEPPS 2-Challenge Rule and explored candidates' critical thinking, analytical decision making, and response to stress. Participating applicants were evaluated using an outcomes-based checklist targeting desired responses. We also sent applicants a post-National Resident Matching Program survey to assess their perceptions of the simulation's value and educational utility. RESULTS: A total of 90 applicants (75% of all applicants) participated in the simulation, which taught residents about important patient safety concepts and provided the program with real time information about their critical thinking ability. All applicants were confident or very confident that they would both speak up and know what to say if they encountered a patient safety breach as a result of participating in this exercise. Simulation performance affected desirability status for 35% of participating applicants, where 23% of applicants ranked higher, and 12% ranked lower compared to baseline application status. CONCLUSIONS: Cognitive simulation training was useful in assessing resident applicant higher-order thinking skills and in helping stratify candidates in conjunction with standard application metrics.